PENGARUH UKURAN PERUSAHAAN DAN RISIKO KEUANGAN PADA PRAKTIK PERATAAN LABA DENGAN VARIABEL PEMODERASI JENIS INDUSTRI - Ratih Maristanda Sidartha, Ayu; Adi Erawati, Ni Made (E-Jurnal Akuntansi; Vol 20 No 2 (2017), 2017)
Earnings were stable over giving a security guarantees in investing and has a good future of the company in the long term and be a reference to make the practice of smoothing earnings. This study aims to determine the effect of firm size and financial risk on income smoothing practices by type of industry as moderating variables. 78 samples selected by purposive sampling method. The hypothesis tested using logistic regression analysis to test the interaction or referred to Moderated Regression Analysis (MRA). The result of the analysis is the size of the company's negative impact on the practice of smoothing earnings, while the financial risk has no significant effect on the income smoothing practices. Effect of firm size on income smoothing practices capable in moderation with a variable type of industry, and the influence of financial risks on income smoothing practices capable in moderation by industry type variable.
Keywords: Income Smoothing, Company Size, Financial Risk, Type of Industry